Broadly neutralizing antibodies in HIV-1 treatment and prevention - Rajesh Kumar; Huma Qureshi; Suprit Deshpande; Jayanta Bhattacharya (SAGE Publishing, 2018)
Antibodies that naturally develop in some individuals infected with human immunodeficiency virus 1 (HIV-1) and are capable of broadly neutralizing diverse strains of HIV-1 are useful for two applications: they can inform the rational design of vaccine immunogens, and they may be capable of preventing and treating HIV-1 infection when administered passively. A phase IIb study has been initiated with the experimental broadly neutralizing antibody (bnAb) VRC01, which has considerable breadth and potency (also referred to as a phase IIb HVTN 703/HPTN 081 and HVTN 704/HPTN 085 AMP efficacy trials) to evaluate its protective efficacy in individuals at risk of HIV acquisition. bnAbs prevent HIV-1 infection by selectively targeting vulnerable sites on the viral envelope (Env) protein that facilitates the entry of HIV. Although in very early stages, bnAbs capable of neutralizing a broad range of inter- and intraclade HIV-1 isolates have been demonstrated to have potential in treating patients either alone or in combination with antiretroviral drug therapy (cART); however, they are proposed to be advantageous over the latter as far as durability and side effects are concerned. Recent studies have indicated that combination therapy of potent bnAbs along with latency-reversing agents (LRAs) might also target latent reservoirs of HIV and kill them by recruiting effector cells, such as natural killer cells, thus confirming clinical progression. Possession of such qualities makes these new-generation potent bnAbs extremely valuable in effectively complementing the shortcomings of current ART drugs and improving the quality of life of infected individuals.